Utilization Pattern and Value of Medicinal and Food Plants Use in the Bidayuh Communities in Bau, Kuching, and Serian Districts of Sarawak - Vivian, Patrick (UNIMAS, 2025)
Bidayuh communities are recognized for their skills in the usage of wild plants for food and traditional medicine. The research was conducted from April 2019 until the end of 2021. The research is done to (1) to gather the pattern of use of medicinal and food plants among Bidayuh communities in Siburan district (Serian Division), Padawan sub-district, and Bau district (in Kuching Division), (2) compare and describe the use practices such as plant parts used and methods of preparation of plants documented, and (3) estimate the annual value of the use of the food and traditional medicinal plants in the communities. Household surveys were conducted on 226 households based on stratified random sampling. Key informant in-depth interviews and group meetings were used to gather further information. A total of 43 medicinal plant species used to treat 25 ailments have been recorded from all districts. Five primary ailments are fever (11 plant species), wound (10 plant species), post-partum care (eight plant species), hypertension (seven plant species), and diseases of the skin (seven plant species). For the food plants, 74 species were recorded from the three districts. The plants are mostly consumed directly as ulam or ripe fruit (36 plant species), cooked as vegetables (28 plant species), and others are made as tuak or condiment (10 plant species).